1999
DOI: 10.1515/bc.1999.042
|View full text |Cite
|
Sign up to set email alerts
|

Chaperones Involved in Hepatitis B Virus Morphogenesis

Abstract: Little is known about host cell factors necessary for hepatitis B virus (HBV) assembly which involves envelopment of cytosolic nucleocapsids by the S, M and L transmembrane viral envelope proteins and subsequent budding into intraluminal cisternae. Central to virogenesis is the L protein that mediates hepatocyte receptor binding and envelopment of capsids. To serve these topologically conflicting roles, L protein exhibits an unusual dual membrane topology, disposing its N-terminal preS domain inside and outsid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
54
0
1

Year Published

2004
2004
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(58 citation statements)
references
References 34 publications
3
54
0
1
Order By: Relevance
“…42 Thus, PDI in fractions 16 and 17 corresponds to the Golgi-associated protein. Immunoblotting of the subcellular fractions for the early endosomal marker protein Rab5B showed that endosomes were mainly present in the lighter fractions of the gradient (fractions [14][15][16][17] (Fig. 6).…”
Section: Vcvs Cofractionate With Microsomesmentioning
confidence: 99%
See 1 more Smart Citation
“…42 Thus, PDI in fractions 16 and 17 corresponds to the Golgi-associated protein. Immunoblotting of the subcellular fractions for the early endosomal marker protein Rab5B showed that endosomes were mainly present in the lighter fractions of the gradient (fractions [14][15][16][17] (Fig. 6).…”
Section: Vcvs Cofractionate With Microsomesmentioning
confidence: 99%
“…Recently, some chaperones and ␥2-adaptin were identified as host factors participating in HBV progeny formation. [16][17][18] Viruses exploit a broad arsenal of strategies to assemble and bud within cells. For example, Pox-like, Irido-like, and Asfar-like viruses induce the formation of "aggresomes," which serve as scaffolds to concentrate structural components.…”
mentioning
confidence: 99%
“…Following SV40 or adenovirus type 5 infections, Hsc 70 was found to be the main virus-induced member of the Hsp70 family (Sainis et al, 1994). Hsc70 was found to interact with the L protein of hepatitis B virus, playing a crucial role in virus morphogenesis by regulating L protein translocation (Prange et al, 1999). Among heat shock proteins genes, in Hsp 20.4 transcript level was equal at 6 hpi in resistant and susceptible race and further constitutively expressed at low level in the resistant silkworm races up to 60 hpi.…”
Section: Discussionmentioning
confidence: 99%
“…Combined factorsV and VIII deficiency (Nichols et al, 1998) Ergic-53 -Spondyloepiphyseal dysplasia tarda (Gedeon et al, 1999) SEDL (sedlin) -Viral Infections: Selected examples that are known to be associated with CNX/CRT quality control AIDS (Land and Braakman, 2001) 160/120 + CNX/CRT Herpes simplex-1 (Yamashita et al, 1996b) B, C and D + CNX/CRT Cytomegalovirus diseases (Yamashita et al, 1996a) B + CNX Influenza Haemagglutinin + CNX/CRT Hepatitis B (Prange et al, 1999) M + CNX Hepatitis C (Choukhi et al, 1998) E1 and E2 + CNX/CRT Rubella (Nakhasi et al, 2001) E1 and E2 + CNX/CRT Measles (Bolt, 2001) Haemagglutinin/Fusion + CNX/CRT Newcastle disease (McGinnes and Morrison, 1998) Haemagglutinin-neuraminidase + CNX Dengue hemorrhagic fever (Wu et al, 2002) M, E and NS1 + CNX Japanese encephalitis (Wu et al, 2002) M, E and NSI + CNX Uukiniemi virus infenction (Veijola and Pettersson, 1999) G1 and G2 + CNX/CRT Vesicular somatitis (Cannon et al, 1996) G + CNX/CRT δ where the defects are in the trimming and modification of the core oligosaccharide which had already been transferred to the target proteins.…”
Section: Iii: Defective Transport Machinerymentioning
confidence: 99%